Clinicopathological correlations in heart transplantation recipients complicated by death or re-transplantation - McDonald, Michelle M.; Mihalj, Maks; Zhao, Bihong; Nathan, Sriram; Matejin, Stanislava; Ottaviani, Giulia; Jezovnik, Mateja K.; Radovancevic, Rajko; Kar, Biswajit; Gregoric, Igor D.; Buja, L. Maximilian (Frontiers in Cardiovascular Medicine, 2022)
Purpose This study aimed to identify and correlate pathological findings with clinical outcomes in patients after orthotopic heart transplantation (OHT) who either died or underwent a re-transplantation. Methodology and study design Single-center retrospective analysis of primary OHT patients who died or were re-transplanted between October 2012 and July 2021. Clinical data were matched with corresponding pathological findings from endomyocardial biopsies on antibody-mediated rejection, cellular rejection, and cardiac allograft vasculopathy. Re-assessment of available tissue samples was performed to investigate acute myocardial injury (AMI) as a distinct phenomenon. These were correlated with clinical outcomes, which included severe primary graft dysfunction. Patients were grouped according to the presence of AMI and compared. Results We identified 47 patients with truncated outcomes after the first OHT. The median age was 59 years, 36 patients (76%) were male, 25 patients (53%) had a prior history of cardiac operation, and 21 patients (45%) were supported with a durable assist device before OHT. Of those, AMI was identified in 22 (47%) patients (AMI group), and 25 patients had no AMI (non-AMI group). Groups were comparable in baseline and perioperative data. Histopathological observations in AMI group included a non-significant higher incidence of antibody-mediated rejection Grade 1 or higher (pAMR ≥ 1) (32% vs. 12%, P = 0.154), and non-significant lower incidence of severe acute cellular rejection (ACR ≥ 2R) (32% vs. 40%, P = 0.762). Clinical observations in the AMI group found a significantly higher occurrence of severe primary graft dysfunction (68% vs. 20%, P = 0.001) and a highly significant shorter duration from transplantation to death or re-transplantation (42 days [IQR 26, 120] vs. 1,133 days [711–1,664], P < 0.0001). Those patients had a significantly higher occurrence of cardiac-related deaths (64% vs. 24%, P = 0.020). No difference was observed in other outcomes. Conclusion In heart transplant recipients with a truncated postoperative course leading to either death or re-transplantation, AMI in endomyocardial biopsies was a common pathological phenomenon, which correlated with the clinical occurrence of severe primary graft dysfunction. Those patients had significantly shorter survival times and higher cardiac-related deaths. The presence of AMI suggests a truncated course after OHT.